2008
DOI: 10.1111/j.1365-294x.2008.03994.x
|View full text |Cite
|
Sign up to set email alerts
|

The biogeography of Miniopterus bats (Chiroptera: Miniopteridae) from the Comoro Archipelago inferred from mitochondrial DNA

Abstract: The endemic fauna of the Comoro Archipelago is composed of a mixture of taxa originating from Africa and Madagascar. Bats are the only native land dwelling mammals on this archipelago, but the biogeographical origins for the vast majority of species within this group are ambiguous. We report here genetic analyses based on two mitochondrial DNA markers to infer the origin of Comorian bats belonging to a reputed species complex of Miniopterus that is further distributed across Africa and Madagascar. Phylogenetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 48 publications
7
50
0
Order By: Relevance
“…Previous research using only mitochondrial data suggested that M. manavi in Madagascar and the Comoros represented unique lineages. However, sampling was limited and the relationships between clades were not fully resolved (Weyeneth et al 2008). Using increased geographic sampling and morphological comparisons of type specimens, each of the clades was more clearly defined.…”
Section: Conservation In the Era Of Molecular Phylogeneticsmentioning
confidence: 99%
“…Previous research using only mitochondrial data suggested that M. manavi in Madagascar and the Comoros represented unique lineages. However, sampling was limited and the relationships between clades were not fully resolved (Weyeneth et al 2008). Using increased geographic sampling and morphological comparisons of type specimens, each of the clades was more clearly defined.…”
Section: Conservation In the Era Of Molecular Phylogeneticsmentioning
confidence: 99%
“…2. Miniopterus griveaudi Harrison, 1959-this taxon was originally described from Grande Comore in the Comoros Archipelago as a subspecies of M. minor, but recent molecular work has shown that these two taxa are not phylogenetically closely related (Goodman et al, 2009b;Weyeneth et al, 2008). The holotype is BMNH 67.1231 and it has a forearm length of 37.8 mm (Harrison, 1959).…”
Section: Taxonomic Considerationsmentioning
confidence: 99%
“…MORPHOLOGICAL AND MORPHOMETRIC COM-PARISONS: There are at least six species of diminutive Miniopterus within the Malagasy region (Madagascar and the Comoros Archipelago) (Goodman et al, , 2009bWeyeneth et al, 2008): M. petersoni (average forearm length of 39.8 mm, range 38-43 mm); M. manavi sensu stricto (average forearm length of 38.6 mm, range 38-39 mm); M. griveaudi (average forearm length of 36.9 mm, range 35-38 mm); M. aelleni (average forearm length of 38.8 mm, range 35-41 mm); M. brachytragos (average forearm length of 36.6 mm, range 35-38 mm); and M. mahafaliensis (average forearm length of 37.4 mm, range 35-38 mm) (all of these measurements were made by the same collector, with the exception of M. manavi). Of these six species, four are endemic to Madagascar and the other two (M. aelleni and M. griveaudi) restricted to Madagascar, Anjouan, and Grande Comore.…”
Section: Miniopterus Mahafaliensis New Speciesmentioning
confidence: 99%
See 2 more Smart Citations